PERANCANGAN WEBSITE SEKOLAH MENENGAH PERTAMA DWIJENDRA BUALU - I Komang Widia Pratama; Made Agung Raharja; I Gusti Ngurah Anom Cahyadi Putra (Jurnal Pengabdian Informatika, 2025)
In the current digital era, school websites have become an urgent necessity to enhance information accessibility and communication efficiency between schools and all stakeholders, including students, parents, teachers, and the general public. Dwijendra Bualu Junior High School recognizes the importance of having an effective and informative website. However, the school currently lacks a website that meets these needs. This study aims to design a structured website tailored to the needs of Dwijendra Bualu Junior High School. The research methodology includes needs analysis, design, and evaluation. The results indicate that the designed website can improve information accessibility, strengthen the school's image, and support technology-based learning processes. Additionally, the website is expected to enhance school administrative efficiency and strengthen the relationship between the school and the community.